Pemanfaatan Bahan Ajar Digital Berbasis Android terhadap Motivasi Belajar Mahasiswa Universitas Terbuka - Wildoms Sahusilawane; Lilian Sarah Hiariey (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The rapid advancement of information and communication technology has transformed learning paradigms in higher education, particularly through the implementation of flexible digital learning systems that emphasize student learning autonomy. Higher education institutions providing distance education face challenges in delivering digital learning materials that are not only easily accessible but also capable of sustainably enhancing students’ learning motivation. The research problem addressed in this study focuses on the extent to which the utilization of Android-based digital learning materials influences the learning motivation of students at Universitas Terbuka. The purpose of this study is to analyze the effect of using Android-based digital learning materials on students’ learning motivation in the context of distance education. A quantitative approach was employed using a survey method as the research design. The research sample consisted of 97 Universitas Terbuka students from UT Ambon, UT Gorontalo, and UT Makassar, selected through simple random sampling. Data were collected using structured questionnaires, while data analysis was conducted through simple linear regression with the assistance of SPSS software. The results of the analysis indicate that the utilization of Android-based digital learning materials has a positive and significant effect on students’ learning motivation, as evidenced by a regression coefficient value of 0.442 and a significance value of 0.000, which is below the 0.05 significance threshold. These findings confirm that improvements in the intensity and quality of using Android-based digital learning materials are directly associated with increased student learning motivation. The novelty of this study lies in strengthening empirical evidence on the effectiveness of Android-based digital learning materials in a cross-regional distance education context, while also providing practical contributions to the development of digital learning strategies aimed at enhancing the learning motivation of Universitas Terbuka students.